Pengaruh Perubahan Kadar Air Tanah Terhadap Tingkat Keamanan Lereng Sepanjang Ruas Jalan Lokoboko-Lokapere Kabupaten Ende - Radja, Veronika Miana; Ndale, Fransiskus Xaverius; Suku, Yohanes laka (TEKNOSIAR, 2023)
The conversion of land functions in the slope area which was previously a protected forest and then being cut to make roads will certainly affect the level of stability. High intensity rains will also affect the increase in surface runoff which will erode the surface of the slopes and erosion. To prevent this from happening, it is necessary to study the safety level of the slopes along the Lokoboko-Lokipere road due to changes in soil water content. Soil sampling is carried out by taking disturbed soil and undisturbed soil and testing soil properties, among others; soil consistency, analysis of specific gravity, cohesion, and shear angle with the addition of 25%, 50%, 75%, and 100% of the initial moisture content. The results of this test show that physically the soil samples on the Lokoboko-Lokipere road section of Ende Regency are classified in soil group A-2-5, namely in the form of gravel and sandy soils that are silt or loamy. Meanwhile, according to USCS, the soil can be classified as silty sand (SM). Mechanically. For slopes with a height of 10 m, it is not safe to add water to 100% of the initial condition (wi), SF=0.996. For a 20 m high slope, it is no longer safe from the initial conditions, SF=0.950. The failure plane for slopes with a height of 10 m is deeper than the failure plane for slopes with a height of 20 m.